2012
DOI: 10.1371/journal.pone.0036375
|View full text |Cite
|
Sign up to set email alerts
|

Do Termites Avoid Carcasses? Behavioral Responses Depend on the Nature of the Carcasses

Abstract: BackgroundUndertaking behavior is a significant adaptation to social life in enclosed nests. Workers are known to remove dead colony members from the nest. Such behavior prevents the spread of pathogens that may be detrimental to a colony. To date, little is known about the ethological aspects of how termites deal with carcasses.Methodology and Principal FindingsIn this study, we tested the responses to carcasses of four species from different subterranean termite taxa: Coptotermes formosanus Shiraki and Retic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…Corpse removal (necrophoresis in a narrow sense) is prevalent in honey bees 6 and ants 5, 22, 34, although burial (covering the dead) 15 and cannibalism (intraspecific necrophagy) 35 were also documented in ants. In contrast, undertaking responses are more complex in termites than eusocial hymenopterans 7.…”
Section: Behavioral Responses Toward Corpsesmentioning
confidence: 99%
See 3 more Smart Citations
“…Corpse removal (necrophoresis in a narrow sense) is prevalent in honey bees 6 and ants 5, 22, 34, although burial (covering the dead) 15 and cannibalism (intraspecific necrophagy) 35 were also documented in ants. In contrast, undertaking responses are more complex in termites than eusocial hymenopterans 7.…”
Section: Behavioral Responses Toward Corpsesmentioning
confidence: 99%
“…To maintain healthy colonies, eusocial hymenopterans (bees, wasps, ants) and isopterans (termites) have evolved sophisticated mechanisms to counter the threat of epidemic disease at both the individual and colony level, including active immune responses and behavioral adaptations 3, 4. Corpse management, also anthropomorphically known as undertaking behavior, is one of the most intriguing innate behaviors in social insects 5-7.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Shelton et al (2005) observed a lack of transfer of permethrin among nestmates of R. flavipes in laboratory trials, as the repellent properties of pyrethroid on donor termites inhibited social interactions from healthy termites. The mortality of recipient workers in the current study might be associated with secondary contamination caused by the accumulation of donor carcasses and their associated fungus growth, carcass handling by healthy termites, or a crowding effect, as found for Reticulitermes (Neoh et al 2012b, Shelton 2012.…”
Section: Discussionmentioning
confidence: 69%